Paliativní péče o lidi s handicapem - Macková, Marie (Univerzita Pardubice, 2013)
Palliative care has experienced great development in recent years. Professional societies are putting pressure on governments to palliative care has become one of the human rights. Needs of patient with physical, mental or intellectual disabilities or patients with several diseases are traditionaly overlooked in palliative care and their needs at the end-of-life are underestimated. In this paper we focus on this particular group of patients and point out that the concept of palliative care can be used in all patients, redardless of their condition or age.
Palliative care for people with disabilities
Keywords: palliative care; disabilities; decisions making; end-of-life care; vulnerability